2020
DOI: 10.1097/spv.0000000000000972
|View full text |Cite
|
Sign up to set email alerts
|

Small Fiber Polyneuropathy Is Associated With Non–Bladder-Centric Interstitial Cystitis/Bladder Pain Syndrome Patients

Abstract: Objectives Interstitial cystitis/bladder pain syndrome (IC/BPS) comprises at least 2 phenotypes. Bladder centric patients typically demonstrate low bladder capacity (BC), often with Hunner lesion (HL), whereas non–bladder-centric patients typically have normal cystoscopic findings and more co-occurring nonurologic symptoms/syndromes (NUS), contributing to widespread pain beyond the bladder. Small fiber polyneuropathy (SFPN) is significantly associated with fibromyalgia, a frequent IC/BPS codiagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
10
1
1
Order By: Relevance
“…30 Another recent small study found biopsy + SFN in 64% (7/11) of patients with non-bladder centric interstitial cystitis/bladder pain syndrome (those without classic Hunner's ulcer and with the co-occurrence of other widespread pain beyond the bladder, such as fibromyalgia, migraine, anxiety, and asthma). 31 Overall, our cohort of complex CPP patients with urologic abnormalities associated with autonomic dysfunction on VUDS (detrusor underactivity and/or BNO) were more likely to have a diagnosis of SFN. Pinprick testing, symptoms of urgency, and elevated postvoid residual volume were also associated with SFN.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…30 Another recent small study found biopsy + SFN in 64% (7/11) of patients with non-bladder centric interstitial cystitis/bladder pain syndrome (those without classic Hunner's ulcer and with the co-occurrence of other widespread pain beyond the bladder, such as fibromyalgia, migraine, anxiety, and asthma). 31 Overall, our cohort of complex CPP patients with urologic abnormalities associated with autonomic dysfunction on VUDS (detrusor underactivity and/or BNO) were more likely to have a diagnosis of SFN. Pinprick testing, symptoms of urgency, and elevated postvoid residual volume were also associated with SFN.…”
Section: Discussionmentioning
confidence: 77%
“…Another recent small study found biopsy + SFN in 64% (7/11) of patients with non‐bladder centric interstitial cystitis/bladder pain syndrome (those without classic Hunner's ulcer and with the co‐occurrence of other widespread pain beyond the bladder, such as fibromyalgia, migraine, anxiety, and asthma) 31 …”
Section: Discussionmentioning
confidence: 99%
“…Several small case series studies have reported a similarly high incidence, up to 63%, of SFPN in women with IC/BPS ( 6 , 40 ), even when controlling for comorbid FMS. Further, several of the other disorders, beyond FMS, that commonly co-occur with IC/BPS have also been found to exhibit high rates of SFPN.…”
Section: Introductionmentioning
confidence: 94%
“…Although bladder pain is the defining characteristic, IC/BPS frequently co-occurs with numerous non-urological symptoms and syndromes including psychiatric disorders such as depression, vague symptoms such as chronic fatigue and sleep disturbances, as well as other poorly understood chronic functional pain disorders such as irritable bowel syndrome (IBS), fibromyalgia syndrome (FMS), and migraines ( 5 ). The clustering of these comorbidities, along with evidence stemming from physiologic and anatomic studies, including the high frequency of small fiber polyneuropathy (SFPN) ( 6 ), point to widespread neurologic abnormalities in this patient population. Many of the symptomatic and functional changes described in patients with IC/BPS are related to the autonomic nervous system, i.e., the system responsible for the regulation of a wide variety of bodily systems and functions ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eine Schädigung überwiegend der peripheren kleinen Nerven und myelinisierten (Aδ) Fasern oder der unmyelinisierten C-Fasern, wie sie bei der Small Fiber Polyneuropathie (SFP) auftritt, wurde in kleiner Fallzahl auch bei IC/BPS Patienten beschrieben [57]. Die SFP könnte als Mitbeteiligung bei der IC/BPS auftreten oder auch nur eine Untergruppe der IC/BPS Patienten vorzugsweise vom Nicht-Hunner Type definieren.…”
Section: Small Fiber Polyneuropathieunclassified